2018
DOI: 10.1002/ptr.6074
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling reveals the plausible mechanisms underlying the antitumor and antimetastasis effects of Andrographis paniculata in esophageal cancer

Abstract: Esophageal cancer (EC) is a seriously invasive malignancy with high mortality and poor prognosis. Metastasis of EC is the major cause of mortality. Our studies previously demonstrated that a herbal medicine Andrographis paniculata (AP) significantly suppressed EC growth and metastasis in vitro and in vivo. However, the underlying mechanisms responsible for these effects have not yet been systematically elucidated. In this context, gene expression profiling of AP-treated squamous EC cells (EC-109) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
(57 reference statements)
1
12
1
Order By: Relevance
“…Knockdown of EGFR suppresses the proliferation, migration and invasion of ESCC cells, and increases the percentage of G1 phase cells (Zeng et al, 2019). In fact, EGFR is one of the genes identified in our previous microarray‐based gene profiling study on the antitumor/antimetastatic effects of AP on EC (Li et al, 2018). STAT3 is a transcription factor downstream of EGFR, whose constitutive activation can promote oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of EGFR suppresses the proliferation, migration and invasion of ESCC cells, and increases the percentage of G1 phase cells (Zeng et al, 2019). In fact, EGFR is one of the genes identified in our previous microarray‐based gene profiling study on the antitumor/antimetastatic effects of AP on EC (Li et al, 2018). STAT3 is a transcription factor downstream of EGFR, whose constitutive activation can promote oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…APW downregulates the gene and protein expression of metastasis‐related factors such as transmembrane 4 superfamily member 3 (TM4SF3), human epidermal growth factor receptor 2 (HER2), and chemokine (C‐X‐C motif) receptor 4 (CXCR4; Li et al, 2017; Yue et al, 2015) in EC‐109 cells. It also reduces the expression of genes related to cell growth, differentiation, migration, and proliferation, including epidermal growth factor receptor (EGFR), platelet‐derived growth factor receptor beta (PDGFRB), and the transmembrane protein KIAA1109, in the same cell line (Li et al, 2018). Moreover, we have recently shown that the antimetastatic efficacy of APW on liver metastasis of EC in xenograft‐bearing mice relies, at least partly, on the gut microbiota (Cheung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been studied that andrographolide-induced cell proliferation decrease may be attributed to the inhibition of fatty acid synthesis, iron uptake, protein synthesis, and FLT3 signaling in MV4-11 cells [18]. In esophageal cancer, Andrographis paniculata has also been reported to exert an antitumor effect and is related to multiple signaling pathways including WNT, TGF-β, MAPK, and ErbB pathways [19]. In addition, some studies have found that andrographolide has obvious inhibitory effects on lung, liver, gastric, esophageal, and breast cancers, among others [20], showing good antitumor activity of andrographolide.…”
Section: Introductionmentioning
confidence: 99%
“…Among these herbs, Andrographis paniculata (AP, 穿心蓮), Acanthopanax senticosus (AS, 刺五加), Camellia sinensis (CS, 綠茶), and Hedyotis diffusa (HD, 白花蛇舌草) were shown to have promising anti-cancer-related bioactivities. Aqueous extract of AP has been shown to potently inhibit tumor growth and metastasis in esophageal cancer mice in our previous studies [14–16]. Acanthopanax senticosus (AS) was investigated for its anti-tumor and immunomodulatory activities in breast cancer cells and immuno-competent mice models [17], unpublished data].…”
Section: Introductionmentioning
confidence: 99%